2023
DOI: 10.3389/fneur.2023.1078926
|View full text |Cite
|
Sign up to set email alerts
|

Improving the models for prognosis of aneurysmal subarachnoid hemorrhage with the neutrophil-to-albumin ratio

Abstract: ObjectiveMany peripheral inflammatory markers were reported to be associated with the prognosis of aneurysmal subarachnoid hemorrhage (aSAH). We aimed to identify the most promising inflammatory factor that can improve existing predictive models.MethodsThe study was based on data from a 10 year retrospective cohort study at Sichuan University West China Hospital. We selected the well-known SAFIRE and Subarachnoid Hemorrhage International Trialists’ (SAHIT) models as the basic models. We compared the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, the overburdened risk of mortality in patients with aSAH persists for much longer than one year, necessitating urgent studies on the prognosis of aSAH. Several studies have revealed the association between NAR and complications and 3-months poor outcomes [ 18 , 20 , 25 , 38 ]. In the absence of long-term follow-up, however, the predictive value of NAR for the long-term prognosis of aSAH was null.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overburdened risk of mortality in patients with aSAH persists for much longer than one year, necessitating urgent studies on the prognosis of aSAH. Several studies have revealed the association between NAR and complications and 3-months poor outcomes [ 18 , 20 , 25 , 38 ]. In the absence of long-term follow-up, however, the predictive value of NAR for the long-term prognosis of aSAH was null.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from individual inflammatory markers, comprehensive immune parameters may detect more subtle changes in peripheral blood associated with the prognoses of aSAH, which involve more extensive information and may compensate for the limitations of using a single blood indicator. In a retrospective cohort study spanning 10 years, Zhang et al ( 51 ) highlighted the importance of inflammatory indicators in predicting aSAH prognosis. Their results demonstrated that incorporating the neutrophil-to-albumin ratio into existing prediction models, such as SAFIRE ( 52 ) and SAHIT ( 53 ), significantly improved the ability to predict the 3-month mortality of aSAH patients.…”
Section: Application Of Peripheral Blood Biomarkers In Ruptured Intra...mentioning
confidence: 99%